Wage Shocks and North American Labor-Market Integration - Robertson, Raymond (American Economic Review, 2000)
This study uses household-level data from the United States and Mexico to examine labor-market integration. I consider how the effects of shocks and rates of convergence to an equilibrium differential are affected by borders, geography, and demographics. I find that even though a large wage differential exists between them, the labor markets of the United States and Mexico are closely integrated. Mexico's border region is more integrated with the United States than is the Mexican interior. Evidence of integration precedes the North American Free Trade Agreement (NAFTA) and may be largely the result of migration. (JEL F15, F20, J61)